PENGGUNAAN APLIKASI CANVA UNTUK MENIGKATKAN KEMAMPUAN SISWA KELAS 10 SMA NEGERI 6 KUPANG MENULIS POSTER MAKANAN LOKAL - Nomeni, Sarty; Djuli, Labu; Nitbani, Samuel H (Jurnal Lazuardi, 2025)
This study aims to determine the effectiveness of using the Canva application in improving the writing skills of 10th-grade students at SMA Negeri 6 Kupang in creating local food posters. The research method used is Classroom Action Research (CAR) with a qualitative and quantitative approach. Data were collected through observations, interviews, and analysis of students' interview results. Based on Table 1, there are four groups: Orchid, Tulip, Frangipani, and Rose. The average score of all groups is 70%, with a completion rate of 77.27%. The group that ranked first with a score of 80 is the Orchid group, consisting of students with the code names EM, KA, AM, FT, and JM. The second place is shared by the Tulip and Rose groups, both scoring 70. The Tulip group includes PK, EB, IK, MB, YB, and ES, while the Rose group includes DH, ZM, AL, AN, and NL. The group in the last position is the Frangipani group, with a score of 60, consisting of DP, BL, A, DA, TB, and CK. The study concludes that students' learning outcomes after receiving the material are still relatively low, with only 17 students achieving the passing criteria, while 5 students have not yet met the criteria, resulting in an overall completion rate of 77.27%. Thus, the overall average score indicates that the use of the Canva application to enhance the writing skills of 10th-grade students at SMA Negeri 6 Kupang falls into the "good" category.